Comparative Study of Antimicrobial Potentials of Phospholipid Compound Produced by Halophilic and Alkaliphiles Bacillus subtilis isolated from Alkaline Meteorite Crater Lonar lake, India - Shinde VA; Patil RB; Pawar PV (International Journal of Life Sciences, 2017)
Bacillus subtilis has ability to grow in extreme environments like Alkaliphilic, Halophilic. These environmental conditions induce microorganisms to produce varied kinds of antimicrobials which has applications in chemotherapy. Therefore In present study antibiotic producing ability of the halophilic and alkaliphilic Bacillus subtilis were compared by screening the activity of the antimicrobial compound was determined against different microorganisms like, Staphylococcus aureus, E. coli, P. aeruginosa, Candida tropicalis, Candida parapsilosis. The halophilic and alkaliphilic Bacillus subtilis isolates were isolated from Alkaline Meteorite Crater Lake Lonar situated in district Buldhana, India and were subjected to primary screening for antimicrobial compound production. The organisms were enriched in Alkaline and Halophilic NG medium which supports the production of phospholipid antibiotic by respective organism and partial purification was done using thin layer chromatography. The partially purified extract of antimicrobial phospholipid compound from both the organisms were tested against different microorganisms and seen that halophilic Bacillus subtilis showed less antimicrobial activity than alkalophilic Bacillus subtilis isolated from Lonar Lake which are having moderate antibacterial activity against different microorganisms.